Efektivitas Kinerja Badan Penanggulangan Bencana Daerah dalam Pengurangan Risiko Bencana di Wilayah Sulawesi Tenggara - Anang Tripasca, Muhammad; Rosadi, Iqram; Nur Firdaus, Ahlil; Widyastuti, Widyastuti; Zukhrufa Allayna, Maritza (Jurnal Indonesia Sosial Sains, 2022)
Handling cross-sectoral social problems, such as disasters, requires the involvement of many stakeholders. Many examples show that the government's capacity to reduce disaster risk can function well as long as there is enough space for other stakeholders to participate, including the community as the object and subject of actors. The purpose of this study was to obtain a descriptive picture of the efficiency of the performance of the Provincial BPBD in disaster risk reduction in Southeast Sulawesi using qualitative descriptive techniques. Interviews, observations, and literature studies were used to obtain data. Research findings indicate that the services provided by the BPBD of Southeast Sulawesi Province have been effective, as evidenced by the agency's preparedness in dealing with any disasters that occur, the support of competent Human Resources, and the availability of facilities and infrastructure that assist in disaster management. Although the services provided by the Regional Disaster Management Agency of Southeast Sulawesi Province have been running well, there are still obstacles in their implementation. Institutions, environmental conditions, and management policies and practices are among some of the inhibiting factors.